What Drives Tourist Loyalty toward Taiwan as a Tourist Destination? A Lesson Prior to the COVID-19 Pandemic - Carol Yirong Lu; Brendan T Chen; Riauli Susilawaty Hutapea (Politeknik Negeri Bandung, 2022)
This study aims to develop an integrative model of loyalty formation to examine antecedent factors to visiting Taiwan. It clarifies the image of Taiwan as a tourist destination and the factors that differentiate this country from its competitors in terms of the target market. The data was collected from a total of 443 self-administered questionnaires. The responses were examined and analyzed using structural modeling. This study empirically confirms the quality–satisfaction–loyalty model and incorporates destination image and personality into it. The result reveals the direct impact of destination image, personality, service quality, perceived value, and customer satisfaction on destination loyalty. Besides, it affirms that destination image, both directly and indirectly, impacts destination loyalty through the role of destination personality. This study provides managerial implications for tourism industry practitioners in terms of future practical application; it can also serve as a reference for future studies.